Lecturers as Workers? Legal Justice in Performance Allowances and Academic Welfare in Indonesian Universities - Rizal Maula; Dhanni Azier Nanda Dwi Jendra; Vela Retna Widyastuti (Yayasan Lembaga Studi Makwa, 2025)
This study examines whether the government's failure to disburse performance allowances to lecturers in Indonesian public universities violates principles of legal justice and undermines the academic welfare rights of lecturers as professional workers. Using normative legal research, the study employs statutory, conceptual, and case approaches by analyzing Law No. 20 of 2023 on Civil Servants, Minister of Administrative and Bureaucratic Reform Regulation No. 6 of 2022, and documented statements from affected lecturers and government officials reported in credible media outlets. The findings reveal three issues. First, the government's failure to allocate budgets and issue the required Presidential Regulation violated the principle of legality and created structural discrimination between ministries. Second, despite lecturers fulfilling BKD and SKP performance requirements, the state failed to implement the mandated pay-for-performance system, contrary to merit system principles under the Civil Servants Law. Third, this negligence constituted unlawful government conduct (onrechtmatige overheidsdaad) and maladministration under Law No. 37 of 2008, thereby opening legal remedies through administrative and civil proceedings. The study concludes that lecturers should be recognized as workers entitled to equitable remuneration, legal certainty, and protection of their economic rights. Academically, this research contributes to administrative justice scholarship by integrating labour rights and higher education governance perspectives to explain state accountability in lecturer remuneration policies and academic welfare protection.